2021
DOI: 10.22146/jtbb.61927
|View full text |Cite
|
Sign up to set email alerts
|

Potential Screening of Bacteriocinogenic-Lactic Acid Bacteria from Mangrove Sediment of Logending Beach for Fisheries Product Preservation

Abstract: The meat and fisheries products have high nutritional content which is highly ideal for bacterial growth. Lactic Acid Bacteria (LAB) have several potential advantages as a bio-preservative agent in the food industry because they produce antimicrobial substances against pathogenic bacteria e.g. bacteriocin. Our previous study has succeeded in isolating and characterizing LAB from the mangrove sediments of Logending Beach, Kebumen. This present study aimed to determine the activity of bacteriocinogenic-LAB again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Chen et al showed inhibitory activity of Lactobacillus plantarum CKXP13 and CWXP24 against the indicator bacteria even after neutralization pH and degradation of hydrogen peroxide, and these antibacterial substances were confirmed as bacteriocins (Chen et al 2021). In addition, the LABs isolated and screened from the mangrove sediments of Logending Beach, Kebumen by Dyah Fitri Kusharyat, also exhibited antibacterial activity after crude extraction with ammonium sulfate (Kusharyati et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al showed inhibitory activity of Lactobacillus plantarum CKXP13 and CWXP24 against the indicator bacteria even after neutralization pH and degradation of hydrogen peroxide, and these antibacterial substances were confirmed as bacteriocins (Chen et al 2021). In addition, the LABs isolated and screened from the mangrove sediments of Logending Beach, Kebumen by Dyah Fitri Kusharyat, also exhibited antibacterial activity after crude extraction with ammonium sulfate (Kusharyati et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has succeeded in discovering several isolates of "lactic acid bacteria from mangrove sediments at Logending Beach in Jawa Tengah (Kusharyati et al, 2021). This present study aimed to determine the characteristics of LAB isolates from mangrove sediment, bacteriocin activity as an antimicrobial against Staphylococcus aureus and Escherichia coli, and the physicochemical characteristics of bacteriocins.…”
Section: Introductionmentioning
confidence: 93%
“…The liquid culture was centrifuged at 5,480 x g for 15 minutes at 4 °C. The resulting cell-free supernatant (CFS) was separated using the salting-out method by adding ammonium sulfate (Kusharyati et al, 2021). A solution of ammonium sulfate (60%) was slowly added until homogeneous.…”
Section: Production and Extraction Of Bacteriocinsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there still needs to be more research exploring lactic acid bacteria (LAB) from mangrove ecosystems. Kusharyati et al (2021) isolated potential LAB from mangrove sediments in Logending Beach, Central Java (Indonesia). Potential screening is carried out through producing bacteriocins and their antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%